1996
DOI: 10.1080/016502596385703
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Low-risk Prematurity on Maternal Behaviour and Toddler Outcomes

Abstract: This short-term longitudinal research project was designed to compare the maternal behaviour of mothers whose toddlers had been born preterm with the maternal behaviour of mothers whose toddlers had been born at term ; the outcomes for the toddlers were also assessed. Twenty-one toddlers who had been born preterm with low medical risk (1460-2420 grams) were compared with 21 term toddlers who were matched in term s of social class. The heightened maternal responsiveness that had been observed during the rst yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
(77 reference statements)
0
2
0
2
Order By: Relevance
“…Many measures of SES are available (e.g., Blishen, Carroll & Moore, 1987;Entwislea & Astone, 1994;Hollingshead, 1975;Nakao & Treas, 1992). The Hollingshead (1975) Four-Factor Index of Social Status has been one of the most frequently used, proving valuable as a predictor/covariate and/or outcome measure in studies of dyslexia (e.g., Felton, Naylor & Wood, 1990;Shaywitz et al, 1999), premature infants (Barratt, 1996) and psychiatric disorders such as major depression (e.g., Cuffe, Waller, Cuccaro, Pumariega & Garrison, 1995). Cirino et al (2002) found a high inter-measure agreement (range r = .81 to .88) across three SES measures (the Hollingshead Four-Factor Index, the Nakao and Treas Scale and the Blishen, Carroll and Moore Scale) using data from two countries (United States and Canada).…”
Section: Ses Measurementmentioning
confidence: 99%
“…Many measures of SES are available (e.g., Blishen, Carroll & Moore, 1987;Entwislea & Astone, 1994;Hollingshead, 1975;Nakao & Treas, 1992). The Hollingshead (1975) Four-Factor Index of Social Status has been one of the most frequently used, proving valuable as a predictor/covariate and/or outcome measure in studies of dyslexia (e.g., Felton, Naylor & Wood, 1990;Shaywitz et al, 1999), premature infants (Barratt, 1996) and psychiatric disorders such as major depression (e.g., Cuffe, Waller, Cuccaro, Pumariega & Garrison, 1995). Cirino et al (2002) found a high inter-measure agreement (range r = .81 to .88) across three SES measures (the Hollingshead Four-Factor Index, the Nakao and Treas Scale and the Blishen, Carroll and Moore Scale) using data from two countries (United States and Canada).…”
Section: Ses Measurementmentioning
confidence: 99%
“…Several studies have documented that premature infants as well as infants and children with health problems sometimes receive less affection, attention, and/or care from their parents (Baratt, Roach, & Leavitt, 1996;Burgess & Conger, 1978;Burgess & Garbarino, 1983;Hagen, 1999;Mann, 1992;Schepher-Hughes, 1985). Poor or reduced parental care can result in physical (Bugental, Martorell, &Barraza, 2003), behavioral, andemotional (Belsky, 1999;Bornstein & Tamis-LeMonda, 2001;Goldberg, 1997) problems in children.…”
mentioning
confidence: 96%
“…Muitos estudos têm avaliado a interação mãe-criança ex-prematura nos primeiros anos de vida da criança e identificado diferenças em comparação a crianças a termo (Barnard & Kelly, 1990;Barratt, Roach & Leavitt, 1996;Laucht & cols., 1997).…”
unclassified